The Role of Adiwiyata School Stakeholders in Fostering Students' Caring Attitudes towards the Environment at MI Negeri 5 Sukoharjo - Siti Isnaini; Khuriyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
An environmental care should not only be done in the school, but also outside the school’s environment also. Students have an important role for the school, if they take action by looking after their school’s environment well, the school will be clean and comfortable. By looking after the school’s environment, it is a part of environmental care. To form this environmental care, one of the things that can be done is by joining the Green School program. The Green School program has many positive purposes for the students, one of them is to grow the student’s environmental care on their environment.The purpose of this research are to determine the Green School’s plan in growing the environmental care on the 6th grade students at MI Negeri 5 Sukoharjo in their environment, to determine the Green School’s implementation in growing the environmental care on the 6th grade students at MI Negeri 5 Sukoharjo in their environment, to determine the evaluation of Green School Program in growing the environmental care on the 6th grade students at MI Negeri 5 Sukoharjo in their environment. As a result, (1) the plan of MI Negeri 5 Sukoharjo as the Green School in growing the environmental care to their student’s surrounding has two environmental-based formed programs. The programs are environmental cadre and The Clean Friday. (2) the implementation of MI Negeri 5 Sukoharjo in growing the student’s environmental care on their surroundings is by putting an environmental cadre in every class which their tasks will be different based on the cadre’s kind. On Friday, students are obliged to follow the Clean Friday program by cooperate in cleaning their school’s environment. (3) the evaluation of MI Negeri 5 Sukoharjo in growing the student’s environmental care to their environment by using attitude assessment. There are 3 attitude assessments, they are discipline assessment, cooperate, and environmental care.